2018
DOI: 10.5812/aapm.73983
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Local Fibrinogen Administration on Postoperative Bleeding in Open Prostatectomy Surgery

Abstract: BackgroundOpen prostatectomy is still accompanied by some postoperative bleeding. Prescribing fibrinogen to promote clot formation in patients with bleeding is of critical importance. This research studied the effects of local injection of fibrinogen on level of postoperative bleeding in open prostatectomy.MethodsOverall, 44 patients were randomly entered in a study on open prostatectomy. Patients in the intervention group received local injections of 500 mg fibrinogen (20 mL) dissolved in distilled water, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…However, the role of ASA in primary CVD prevention is challenging because of conflicting effects on CVD mortality rates (15). Mounting evidence suggests that the apparent benefits of ASA as a therapy modality for primary CVD prevention outweigh its less significant disadvantages causing the risk of some lifethreatening conditions such as bleeding (16)(17)(18)(19). A metaanalysis of 20 clinical cases including 3000 patients who received ASA as secondary cardiovascular prevention indicated that "aspirin resistance" in 28% of the patients correlated with a four-fold risk of CVD (20,21).…”
Section: Cardiovascular Related Beneficial Effectsmentioning
confidence: 99%
“…However, the role of ASA in primary CVD prevention is challenging because of conflicting effects on CVD mortality rates (15). Mounting evidence suggests that the apparent benefits of ASA as a therapy modality for primary CVD prevention outweigh its less significant disadvantages causing the risk of some lifethreatening conditions such as bleeding (16)(17)(18)(19). A metaanalysis of 20 clinical cases including 3000 patients who received ASA as secondary cardiovascular prevention indicated that "aspirin resistance" in 28% of the patients correlated with a four-fold risk of CVD (20,21).…”
Section: Cardiovascular Related Beneficial Effectsmentioning
confidence: 99%